A previously unknown specimen of the temnospondyl amphibian Parotosuchus bogdoanus (Woodward, 1932) from the Lower Triassic of Eastern Europe - I.V. Novikov; A.V. Uliakhin; V.V. Silantiev (Учёные записки Казанского университета: Серия Естественные науки)
This article reports on the results of a study of a sample from the collection of the Shtukenberg Geological Museum of Kazan Federal University. The sample is the preorbital part of the skull of a large temnospondyl amphibian previously identified as Wetlugasaurus sp. and known from the Triassic of the Volga region. On the basis of the morphology of the palatal surface, it was concluded that the sample belongs to the genus Parotosuchus of the Late Olenekian. The analysis of the host rock helped to determine more precisely its locality (Akhtubinsk district of the Astrakhan region, Bolshoye Bogdo II locality). The specimen under study most likely belongs to P. bogdoanus (Woodward, 1932), first described from this locality, thus making it possible to complete the diagnosis of the species.